Konflik dalam Tradisi Nyumbang (Studi Tradisi Nyumbang Dengan Sistem Pinggelan Di Desa Plana Kecamatan Somagede Kabupaten Banyumas) - KHASANAH, SITI KHOEROTUL; Dadan, Sulyana (Laborataorium Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Jenderal Soedirman, 2022)
Abstract This study aims to explain the conflict in the minggel tradition in the Plana Village, Somagede District, Banyumas Regency with a socio-cultural perspective. The tradition of giving is able to have an influence on social and cultural life for the community, where donation is an inseparable part of social life. Plana Village has three donation systems, namely the pinggelan system, the social gathering system and the regular donation system. The tradition of donating in society does not have a clear written law regarding the donating process, so people only donate according to cultural traditions that have been carried out for generations. The emergence of conflicts in the tradition of donating is caused by a discrepancy in the donating process with what is the goal in donating. The nature of the pekewuh owned by the village community makes them try to donate, even though they are faced with the inability to donate. The tradition of donating has an exchange system for both goods and services used to donate, what is used to donate will return to the donor at a predetermined time. Every donation transaction made by the community has a record book that each person has. The Plana Village community has two forms of donation systems, each of which has differences. Contributing pinggelan and donating arisan, where donations with the pinggelan system are done when the celebration has not yet started, while donating to the arisan system is done when the celebration is in progress. Keywords: Conflict, Minggel, Contributing Pingelan